Linear equations :grade 9 learners’ progress and their difficulties over time - Halley, Andrew (My University, 2019)
This study investigated Grade 9 learners’ progress in solving linear equations over a six month period. The notion of progress is taken to encompass shifts in learners’ abilities to solve equations with fluency, and shifts in communicating their reasoning, Data were collected with six learners in a Johannesburg secondary school, by means of four task-based interviews each.
A dissertation submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirement for the degree Masters of Education by Dissertation Johannesburg, 2019
Keywords: Equations--Study and teaching (Secondary); Mathematics--Study and teaching